Dictionary of the Free Economic Society as a Result of Term Formation in 18th-Century Mineralogy - Ivanova, Elena E.; Shaikhinurova, Diana R. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This article analyses mineralogical nomenclatural terms presented in the 1790 Dictionary of the Imperial Free Economic Society. The choice of the source is conditioned by its special status: it completes the stage of creation of mineralogical terminology in the eighteenth century. The compilers of the dictionary bring together all the terms existing in mineralogical literature and oral tradition, try to organise the terminology, and coin new nomenclature terms. In order to identify the newly created nominations and to determine the position of the authors of the dictionary in relation to the development of mineralogical terminology, the article carries out a comparison of terms from the Dictionary of the Imperial Free Economic Society with the terminology of previous works on mineralogy translated into Russian: W. F. Brickman, I. E. Walch, A. F. Kronstedt, I. G. Lehmann, and I. G. Valerius, and the Dictionary of Commerce. The comparative analysis demonstrates that, following the general trend in the language of science of the eighteenth century, the dictionary compilers try to make the term as clear and accessible to the Russian reader as possible, avoiding new loanwords and preferring Russian equivalents and calques. A distinguishing feature of the new terminology in the Dictionary of the Imperial Free Economic Society is the extensive use of popular names for minerals, along with the objective of single-word terms. This objective is achieved by collapsing term-word combinations through word building and suffixation. The article notes that a characteristic feature of the language of the Russian mineralogy of the eighteenth century is the polysemy of terms. The compilers of the Dictionary of the Imperial Free Economic Society try to overcome it in a way accessible for that time, offering a number of synonyms for polysemantic terms. The innovations of the Dictionary of the Imperial Free Economic Society are an important step towards the formation of comprehensive mineralogical terminology.